Criminalization of the Immigration in the EU and Protection of Procedural Rights - Matić Bošković, Marina (NBP. Nauka, bezbednosti, policija, 2024)
Serbia is a transit country for migrants on their way to the EU via the Western Balkan route. In 2015-2016 over the millions of migrants from Syria, Afghanistan, Iraq, Pakistan, and Somalia used the Western Balkan route to reach the EU countries. Serbia as the EU candidate country has to fulfil requirement of cooperation with the EU in the area of managing migratory flows through efficient control of its borders jointly with the EU officers. For Serbia to reinforce the border management is important to understand the EU migration policy. Although the Tampere European Council Conclusion from 1999 and the European Agenda on Migration from 2015 declared EU commitments to develop legal access to vulnerable individuals, in the practice migration is perceived as a treat for security. As a result of this approach the preventive and repressive criminal law measures were introduced in the immigration law. The European member state authorities are selectively use criminal law to achieve the migration policy goals. The criminal law measures that are applied across the EU are detention, arrest, police control, removal from the territory. However, there is criticism that these criminal law measures are not followed by criminal law guarantees, especially procedural rights and human rights protection instruments. The analysis is put in context of the Return directive 2008/115 that sets the EU standards and procedures on return of illegally staying migrants. In the article author analyses effects of the criminalization of the immigration and development of the Court of Justice jurisprudence in relation to the procedural rights.
Keywords: criminalization of immigration, EU law, Court of Justice jurisprudence, Return Directive, procedural rights